The use of sonication treatment to completely decellularize blood arteries: a pilot study - Noor Azmi, Azran Azhim; Yamagami, K.; Muramatsu, K.; Morimoto, Y.; Tanaka, Masato (2011)
We have developed a novel sonication decellularization system to prepare completely decellularized bioscaffolds in a short treatment time. The aim of the study is to investigate the sonication decellularization efficiency and its relation with ultrasonic power output and dissolved oxygen (DO) concentration in different detergent solution. In the study, we used aorta samples to evaluate sonication decellularization efficiency, which assessed treatment duration, sonication power and SDS detergent with/without saline. The treated samples were evaluated histologically by Hematoxylin Eosin (HE) staining and scanning electron microscopic (SEM) photographs. The concentration of DO was monitored to identify the effect of sonication on cavitation-related DO concentration in the solution. From histological results, the sonication decellularization efficiency was better than the other preparation methods. Decellularization efficiency was tended to increase significantly when DO value decreasing after 6 hours of treatment. In conclusion, we conclude that sonication treatment can be used to prepare the complete decellularized scaffolds in short treatment time.